Escola de tempo integral: avaliação do percurso dos programas Mais Educação e Novo Mais Educação no município de Maracanaú-CE na percepção dos gestores educacionais - Araújo, Antônia Jacqueline Ávila de (2024)
The proposal for full-time schools in Brazil is already present in the Education Guidelines and Bases Law (LDB 9394/96) and in the National Education Development Plan (PNDE-2014-2024) where one of the actions is the expansion of workload in public schools. One of the programs that sought to boost this expansion of the workload is Mais Educação, which over time had two versions, Mais Educação existing between 2007 and 2015, and Novo Mais Educação, implemented in 2016 and discontinued in Maracanaú, the locus of this study, in 2020 due to the Covid-19 pandemic. In view of the above, the general objective of this work is to evaluate the Mais Educação and Novo Mais Educação Programs, and their full-time proposal for comprehensive education, from the perspective of school managers in the municipality of Maracanaú, metropolitan region of Fortaleza, in Ceará. To this end, the methodology was qualitative based on the evaluative perspective of In-Depth Assessment (Rodrigues, 2008, 2011). The time frame occurred between 2007 and 2020. Data collection techniques involved documentary research and the application of a questionnaire with managers. It was then possible to deeply understand the vision that school managers in the city of Maracanaú have in relation to these two Programs. And it was noticed that the first version of the Program was much more comprehensive, working on the macro fields of knowledge, leaving the curricular contents, in an emancipatory perspective. In the second version, the Program lost its broad character and became only tutoring classes, in the subjects of Portuguese Language and Mathematics.